A flowchart of the MC-TAD algorithm for generating the permissible paths inside the first and second cubes representing two neighboring TADs. - Samira Mali (8897903) (2025)
The generated path enters the second cube after it has traversed full segments in the first cube. Because of a directionality of the chromatin chains between TADs and the specified path length in one TAD, a starting face in the first cube cannot coincide with the starting face in the second cube, unless the starting bin belongs to the edge of the cube. The upper right schematic illustrates one of the many permissible paths for the case of N = 2 (8 bins per cube) to approximate its fine structure.